Listeria monocytogenes infections: presentation, diagnosis and treatment. (2021) - Valenti, Maria; Ranganathan, Nisha; Moore, Luke SP; Hughes, Stephen
Abstract : Listeriosis is an infective complication that primarily affects pregnant women, patients at extremes of age or those with weakened immune systems. Ingestion of food contaminated with Listeria monocytogenes is the most common source of infection, causing self-limiting illness in immunocompetent hosts but associated with invasive infection and high mortality in high-risk patient groups. Milder illness presents as gastroenteritis with fever, diarrhoea, nausea and vomiting common in the 7 days post exposure. Invasive infection, characterised by bacteraemia and encephalitis, can develop in high-risk patients. Fetal loss is a major complication of listeriosis during pregnancy. Penicillin-based therapy (high dose penicillin or amoxicillin) in combination with gentamicin is advised for invasive infection; co-trimoxazole may be considered for patients intolerant to penicillin. Vulnerable individuals, notably pregnant women, should be counseled on appropriate preventative strategies including avoiding foods commonly contaminated with L. monocytogenes, such as soft ripened cheeses, pate, cooked chilled meats, unpasteurised milk, and ready to eat poultry unless thoroughly cooked.